Barriers of Implementation of Controlling in the Retail Chains - Kuźniarska, Aneta (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The main goal of the conducted research was to identify the factors constituting a barrier to the implementation of controlling in the retail chains. Quantitative research was carried out using a research tool, which was a questionnaire, containing closed questions addressed to employees of retail chains, mainly specialists from controlling departments, HR, managers at various levels and directors. The research was carried out in large networks with the participation of Polish and foreign capital. The results of the research have shown that the most important barrier to the implementation of controlling is the too low level of knowledge in organizations on how to implement it and the lack of adequate financial resources enabling its implementation. Due to the tightness of retail chains and the fact that up to now there were mainly barriers to the implementation of controlling in production and service units, the topic discussed in the study was considered important.